Testing the Tonic Effect of Gotu Kola (Centella asiatica) Extract on Male White Mice (Mus musculus) Using the Rotarod Method - Wiwin Novitasari; Anita Dwi Septiarini; Bagas Ardiyantoro (CV. AFDIFAL MAJU BERKAH, 2025)
A tonic is a substance or mixture of substances that can strengthen the body or increase a person's energy. The tonic effect is caused by stimulation of the central nervous system (CNS). The herb gotu kola (Centella Asiatica) is a natural substance that contains bioactive compounds such as terpenoids, which play a role in producing the tonic effect. This study aims to analyze the ability of gotu kola herb extract (Centella asiatica) to provide a tonic effect on male white mice (Mus Musculus) and to determine the optimal dose of gotu kola herb extract (Centella Asiatica) to provide an optimal tonic effect. This study used the Rotarod test with treatment groups, each consisting of 5 test animals given Na-CMC 0.5% as a negative control, caffeine 100mg/kgBW as a positive control, and Centella asiatica herb extract suspension at varying doses, namely 50mg/kgBW as a low dose treatment, 100 mg/kgBW as a medium dose treatment, and 150 mg/kgBW as a high dose treatment. Statistical test results showed a significant increase in the time mice remained on the rotarod in all dose treatments compared to the negative control and no treatment. The 150 mg/kgBW dose provided a tonic effect closest to that of caffeine. Phytochemical testing showed that gotu kola herb contains terpenoids, which are thought to play a role in its tonic activity. Thus, gotu kola herb extract has the potential to be developed as a natural tonic alternative.